Injury patterns among elite football players: A media-based analysis over six seasons with emphasis on playing position - Leventer, L.; Eek, F.; Lames, M.; Hofstetter, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
The study objective was to describe types, localizations and severity of injuries among first division Bundesliga football players, and to study the effect of playing positions on injury incidence and severity based on information from public media. Information about exposure and injuries from 1673 players over 6.4 seasons were collected from a media-based register. The knee was the most frequent localization and had the longest recovery time (p<0.001). Recovery following ligament injuries was significantly longer than muscle injuries. Significant differences between the playing positions were found in injury incidence and injury burden (lay-off time per incidence-rate), with wing-defenders sustaining significantly lower incidence-rates of groin injuries compared to forwards (rate ratio: 0.46, 95% CI: 0.21-0.99). Wing-midfielders had the highest incidence-rate and injury burden from match injuries while centre-defenders sustained the highest incidence-rate and injury burden from training injuries. There were also significant differences in match availability due to an injury across the playing positions, with midfielders sustaining the highest unavailability rates from a match and training injury. Injury-risk and patterns seem to vary substantially between different playing positions. Identifying positional differences in injury-risk may be of major importance to medical practitioners when considering preventive measures.